DETERMINATION AND ARGUMENTATION OF JUDGES IN MARRIAGE DISPENSATION AT THE SUMBAWA BESAR RELIGIOUS COURT: ANALYSIS OF DETERMINATION NUMBER 4/PDT.P/2024/PA.SUB REVIEW OF MASLAHAH AL-BUTI AND LEGAL POLITICS - Solikhudin, Muhammad; Faidati, Ashima; Jauhari, Sofuan; Faiz, Muhammad Fauzinudin; Mauwd, Mowafg Abrahem (UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
Marriage is a common instinct for all humans. In Law Number 1 of 1974 concerning Marriage, it is explained that marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal family (household) based on the One Almighty God. As for the age of the prospective bride and groom is 19 years according to Law Number 16 of 2019, but in the Sumbawa Besar Religious Court there was a request for marriage dispensation where the male party was still under 19 years old and there were factors underlying the determination of the Sumbawa Besar Religious Court Number 4/Pdt.P/2024/ PA.Sub that the prospective wife was pregnant outside of marriage, so the judge used Article 7 Paragraph 2 of Law Number 16 of 2019 concerning marriage and PERMA No. 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Requests. This research is a field research, qualitative in nature, with a legislative, conceptual, and case approach. As a result of this research, the judge granted the request for marriage dispensation. This determination is in line with the maslahah of al-Buti and the legal policy of marriage dispensation. The findings in this study, First: there are legal, sociological, and philosophical factors that influence judges in deciding cases. Second: The judge's appointment is in line with the political law of the marriage dispensation and is in line with the maslahah of Muhammad Said Ramadan al-Buti. Third: Finding the idea of ​​maslahah usrah cum urgency, with several working methods, first the judge has asked and examined the applicant's files carefully, second the judge considers the maslahah aspect to be prioritized in determining the marriage dispensation, third the judge is able to apply the legal policy of marriage dispensation, namely the direction of legal policy that contains the benefits and urgency for the parties seeking justice.